KAJIAN ARSITEKTUR MODERN PADA PRASARANA SEKOLAH KEBERBAKATAN OLAHRAGA (SKO) - Tri Wicaksono, Muhmmad Rizki Teguh (Jurnal Arsitektur ZONASI, 2020)
Abstract: Modern Architecture is one of the famous concepts from the past until now. Modern architectural style that eliminates the style of ornamentation is one of the strong characteristics of modern architecture. By making the building more minimalist modern architecture has a good impact on the world of architecture to the present. One of them is modern architecture in infrastructure or sports hall, to achieve good quality facilities becomes a very important role in the world of sports. The application of modern architecture to sports buildings can be seen in the looks and plans of buildings of its sports facilities. The case study used for this research is the Middle School / High School for Sports, Ragunan. By examining some parts of the principles of modern architecture, namely: The use of basic geometric shapes, the use of elements of field and volume lines, the symmetrical impression on buildings, the use of grid systems, the honesty of construction and structure. The conclusion is that the building of a special sports school in the Ragunan has used Modern Architecture from the principles that have been used as well as the results of the analysis. Keywords : Architecture; Modern Architecture; Principal Architecture Abstrak: Arsitektur Modern merupakan salah satu konsep yang terkenal dari dulu hingga sekarang. Gaya arsitektur modern yang menghilangkan corak ornamen merupakan salah satu ciri khas yang kental dari Arsitektur modern. Dengan menjadikan bangunan menjadi lebih minimalis arsitektur modern membawa dampak yang baik pada dunia arsitektur hingga saat ini. Salah satu nya adalah arsitektur modern pada prasarana atau gedung olahraga, untuk mencapai kualitas yang bagus fasilitas menjadi peran yang sangat penting dalam dunia olahraga. Penerapan arsitektur modern pada gedung olahraga bisa terlihat pada tampak dan denah dari bangunan fasilitas olahraga nya. Studi kasus yang dipakai untuk penelitian ini adalah SMP/SMA Sekolah Khusus Olahraga, Ragunan. Dengan meneliti beberapa bagian dari prinsip arsitektur modern yaitu: Penggunaan bentuk dasar geometri, Penggunaan unsur garis bidang dan volume, Kesan Simetris pada bangunan, Penggunaan sistem grid, Kejujuran konstruksi dan struktur. Kesimpulanya bahwa pada bangunan Sekolah khusus olahraga di Ragunan telah menggunakan Arsitektur Modern dari prinsip-prinsip yang telah gunakan serta hasil analisis. Kata Kunci: Arsitektur; Arsitektur Modern; Prinsip Arsitektur